A Three Phase Multi Level Converter For grid Connected PV System - S. Srikanth (Institute of Advanced Engineering and Science, 2014)
Photovoltaic energy is a wide kind of green energy. A high performance on these systems is needed to make the most of energy produced by solar cells. Also, there must be a constant adaptation due to the continuous variation of power production. Control techniques for Power Converters like the MPPT algorithm (Maximum Power Point Tracking) present very good results on photovoltaic chains. Nevertheless, losses on power elements reduce global performance and the voltage/current adaptation is not always possible. This paper presents a single-phase 11-level (5 H-bridges) cascade multilevel DC-AC grid-tied inverter. Each inverter bridge is connected to a 200 W solar panel. OPAL-RT lab was used as the hardware in the loop (HIL) real-time control system platform where a Maximum Power Point Tracking (MPPT) algorithm was implemented based on the inverter output power to assure optimal operation of the inverter when connected to the power grid as well as a Phase Locked Loop (PLL) for phase and frequency match. A novel SPWM scheme is proposed in this paper to be used with the solar panels that can account for voltage profile fluctuations among the panels during the day. Simulation and experimental results are shown for voltage and current during synchronization mode and power transferring mode to validate the methodology for grid connection of renewable resources.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6156